1979
DOI: 10.1017/s0022112079001920
|View full text |Cite
|
Sign up to set email alerts
|

On the perseverance of a quasi-two-dimensional eddy-structure in a turbulent mixing layer

Abstract: Strong external disturbances were introduced into a mixing layer in order to test the formation of the quasi two-dimensional coherent eddies and their survival under less than ideal conditions. Velocity and temperature correlation measurements, flow visualization, and the simultaneous use of a large number of sensors suggest that these eddies are very stable in the range of Reynolds numbers considered and they persevere in spite of the external buffeting imposed. Some measurements were carried out in a mixing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
0
1

Year Published

1981
1981
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(47 citation statements)
references
References 3 publications
3
43
0
1
Order By: Relevance
“…It is interesting to compare our results for the spacing of the streamwise vortices with velocity correlation measurements by Wygnanski et al (1979) and Browand & Troutt (1980). From the measurements of Wygnanski et al a t the centre of the layer, we estimate a value of Az/S, x 0.5 for the location of the minimum cross-correlation coefficient.…”
Section: Discussionmentioning
confidence: 67%
“…It is interesting to compare our results for the spacing of the streamwise vortices with velocity correlation measurements by Wygnanski et al (1979) and Browand & Troutt (1980). From the measurements of Wygnanski et al a t the centre of the layer, we estimate a value of Az/S, x 0.5 for the location of the minimum cross-correlation coefficient.…”
Section: Discussionmentioning
confidence: 67%
“…The effects of turbulence intensity on free-shear flows were investigated by Wygnanski et al [129], who inserted a turbulence generating grid in one of the streams upstream of the trailing edge of a splitter plate. The authors found that roll-up of the shear layer persisted with the increase in FSTI, despite previous hypotheses and results suggesting that free-stream turbulence intensity inhibits two-dimensional roll-up, and rather leads directly to a three-dimensional flow [118].…”
Section: Free Shear Layersmentioning
confidence: 99%
“…Three-dimensional effects appear downstream of the rst few pairings. Experimentally, to isolate these two-dimensional structuresand to study their role, 16,17 the mixing layers can be forced at the frequency corresponding to their natural rollup and its subharmonics.…”
Section: Introductionmentioning
confidence: 99%